Програмно-цільовий підхід до дослідження економічної безпеки підприємства - Степанова, О. В.; Горбач, О. І. (ХНУРЭ, 2014)
An economic security company represented as a multi-level system with closed-loop control. Using a program-based approach developed tree objectives of economic security. We consider the feasibility of using an additive utility function to assess the level of economic security
Keywords: економічна безпека підприємства; дослідження економічної безпеки